Dairy-draught cows performance and implications for adoption - Zerbini, E.; Shapiro, Barry I.; Larsen, C.E.S.; Gebre-Wold, A. (South African Society of Animal Science, 1996)
Smallholder whole-farm productivity could be increased, and a more sustainable farming system could be established, if dairy cows could also be used for draught work. On-station results over a three-year period indicated that when dairy-draught cows were adequately fed, milk production was not significantly affected. However, conception was delayed. The economic potential of the use of dairy-draught cows was substantiated with the ILRI bio-economic herd model which showed that the value of work more than compensated for the small reduction in milk production, longer calving interval and greater feed costs found in working cows. However, cultural attitudes could be obstacles to the adoption of dairy-draught cows. An anthropological survey showed that despite reservations many farmers were willing to try cows for milk and draught work. While in the medium term the technical feasibility as well as social factors will affect the acceptance of cow traction technologies, in the long run the diffusion of dairy-draught cows will depend on the public support for dairy Development. A follow-up on-farm study investigated the production performance of F1 Friesian x Boran cows used by farmers in the Ethiopian Highlands mixed crop-livestock farming systems. Over a period of two years, milk production of dairy-draught cows was 2620 kg, and calving interval was 525 days. First lactation average milk yield and days in milk were 1,864 kg and 376 days, respectively. Over a period of two years cows worked an average of 26 days/year.